The system of juvenile criminal justice during the state of emergency (COVID-19) - Echegaray Bernaola, Luzmila Violeta (2020)
The legal framework of the state of emergency needs to guarantee the system of juvenile criminal justice, since juveniles are vulnerable because of their age and as such they need a program of social reinsertion. Furthermore, in this legal regimen and this social context, the person remains with free exercise of rights prohibiting the freedom of movement only.